Assessment of Autism Spectrum Disorder : Critical Issues in Clinical, Forensic and School Settings - Kroncke, Anna P.; Willard, Marcy; Huckabee, Helena (Cham : Springer, 2016)
This book examines current and emerging techniques for the dynamic and evolving field of autism assessment. It provides a detailed, research-based discussion of the latest innovations in assessment from a practical perspective accumulated from decades of autism assessment and treatment training and experience in both educational and clinical settings. The book provides personal insights into the engaging and intriguing autism population and case studies of children who have captured the hearts and minds of clinicians nationwide. As the rates of autism have grown more than 10-fold during the past decade, researchers have questioned whether unclear diagnostic guidelines may be to blame for the high numbers of recently diagnosed children. Rather, the authors argue, tighter agreed upon methods for diagnosis of autism have allowed for more accurate identification of children who indeed require supportive treatments and therapies. This unique volume provides readers with clarity about best-practice assessment approaches from sequential and pragmatic perspectives as well as an understanding of critical issues and hurdles in ascertaining the appropriate diagnosis. In addition, myriad potential comorbid conditions or differential diagnoses are addressed. This book is a must-have resource for clinicians and practitioners as well as researchers and graduate students in the fields of child and school psychology, behavioral therapy, social work, psychiatry, pediatrics, forensic psychology, and educational and healthcare policy.
Part 1: Understanding Autism -- Chapter 1. What is Autism? History and Evaluation -- Chapter 2. The Causes of Autism -- Chapter 3. The Causes of Autism -- Chapter 3. Optimal Outcomes and Recovery -- Chapter Autism in the DSM-5 -- Part 2: Conducting an Evaluation -- Chapter 5. Referral and Initial Consult -- Chapter 6. Testing Begins -- Chapter 7. Comprehensive Evaluation -- Part 3: Data Analysis -- Chapter 8. Cognitive and Language Assessment -- Chapter 9. Social and Sensory Assessment -- Chapter 10. Visual, Spatial, and Motor Assessment -- Chapter 11. Attention, Executive Functions, and Memory Assessment -- Chapter 12. Emotions, Mood, Behavior, and Adaptive Assessment -- Part 4: Differential Diagnosis -- Chapter 13. Disorders of Neurodevelopment and Brain Functioning -- Chapter 14. Disorders of Emotion, Mood, and Behavior -- Part 5: Concluding the Assessment Process -- Chapter 15. Feedback, Report, and Recommendations -- Chapter 16. Case Examples from Referral to Recommendation -- Part 6: Assessment in Applied Settings and Special Testing Considerations -- Chapter 17. Forensic Assessment for Autism Spectrum Disorder -- Chapter 18. School-Based Assessment -- Chapter 19. School, Parents, and Community Partnerships -- Chapter 20. Assessment Across the Lifespan.
Keywords: Child psychology; School psychology; Child and School Psychology